2009
DOI: 10.1038/sj.bjc.6605480
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer cells modulate osteoblast mineralisation and osteoclast differentiation through Id-1

Abstract: BACKGROUND: Id-1 is overexpressed in and correlated with metastatic potential of prostate cancer. The role of Id-1 in this metastatic process was further analysed. METHODS: Conditioned media from prostate cancer cells, expressing various levels of Id-1, were used to stimulate pre-osteoclast differentiation and osteoblast mineralisation. Downstream effectors of Id-1 were identified. Expressions of Id-1 and its downstream effectors in prostate cancers were studied using immunohistochemistry in a prostate cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 56 publications
3
14
0
Order By: Relevance
“…Osteoblasts are the cells responsible for the formation and mineralization of new bone. We and others have previously shown that osteoblasts are stimulated by PC tumor cells . In addition, we demonstrated that osteoblasts induce a more aggressive phenotype along with osteomimicry in osteoblastic CRPC cells .…”
Section: Introductionsupporting
confidence: 73%
“…Osteoblasts are the cells responsible for the formation and mineralization of new bone. We and others have previously shown that osteoblasts are stimulated by PC tumor cells . In addition, we demonstrated that osteoblasts induce a more aggressive phenotype along with osteomimicry in osteoblastic CRPC cells .…”
Section: Introductionsupporting
confidence: 73%
“…Immunohistochemical staining was performed as previously described using the Dako Envision system (Dako, Glostrup, Denmark) 32. Pea3 antibody (Santa Cruz Biotechnology, Santa Cruz, CA, USA) was used at a dilution of 1 : 50 and Snail antibody (Cell Signaling, Danvers, MA, USA) was used at a dilution of 1 : 100.…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted by Lee et al reported that the positive expression regulation of Id‐1 can be combined with Ets and inhibit the activity of P16 INK4ɑ , while the latter can promote the phosphorylation of Rb protein. Id‐1 can also form heterodimers to inhibit E2A from activating p21 through specific binding with E2A, while the latter can activate CDK2 to phosphorylate Rb protein and guarantee the successful procession of the G 1 /S phase . In addition, it has been found in bone cell cancer that Id‐1 activates cell growth and promotes cell proliferation by activating the MAPK of Raf‐1 .…”
Section: Discussionmentioning
confidence: 99%
“…8,9 A study conducted by Lee et al 10 also form heterodimers to inhibit E2A from activating p21 through specific binding with E2A, while the latter can activate CDK2 to phosphorylate Rb protein and guarantee the successful procession of the G 1 /S phase. 11 In addition, it has been found in bone cell cancer that Id-1 activates cell growth and promotes cell proliferation by activating the MAPK of Raf-1. 12 Furthermore, it has been found in gastric cancer and pancreatic cancer cells that the Id-reverse target-nuclear factor κB (NF-κB) pathway is activated to promote the expression of Bcl-2, inhibit the TNF-ɑ pathway, decrease the expression level of caspase-3, and inhibit tumor cell death.…”
Section: Discussionmentioning
confidence: 99%